From southern refugia to the northern range margin: genetic population structure of the common wall lizard, Podarcis muralis. (12th April 2013) - Gassert, Franz; Schulte, Ulrich; Husemann, Martin; Ulrich, Werner; Rödder, Dennis; Hochkirch, Axel; Engel, Edmée; Meyer, Jobst; Habel, Jan Christian
Abstract: Aim: Thermophilic species persisted in southern refugia during the cold phases of the Pleistocene, and expanded northwards during warming. These processes caused genetic imprints, such as a differentiation of genetic lineages and a loss of genetic diversity in the wake of (re)colonization. We used molecular markers and species distribution models (SDMs) to study the impact of range dynamics on the common wall lizard, Podarcis muralis, from southern refugia to the northern range margin. Location: Parts of the Western Palaearctic. Methods: We genotyped 10 polymorphic microsatellites in 282 individuals of P. muralis and sequenced the mitochondrial DNA (mtDNA) cytochrome  b gene to study the genetic structure, divergence times and ancestral distributions. Furthermore, we generated SDMs for climate scenarios for 6 and 21 ka derived from two different global circulation models. Results: We detected two major mtDNA lineages – a western France clade (Pyrenees to Brittany), and an eastern France clade (southern France to Germany, Belgium and Luxembourg). This split was dated to c . 1.23 Ma. The latter clade was divided into two subclades, which diverged c . 0.38 Ma. Genetic diversity of microsatellites within each clade was nested and showed a significant loss of genetic diversity from south to north, a strong pattern of allele surfing across nearly all loci, and an increase in genetic differentiation towards the northern range margin. Results from SDMs suggest that southward range retraction during the late glacial period split the distribution into geographically distinct refugia. Main conclusions: The strong genetic differentiation mirrors the effects of long‐term isolation of P. muralis in multiple refugia. Post‐glacial recolonization of Northern Europe has taken place from two distinct refugia, most probably along river systems (Rhône, Rhine, Moselle) and along the Atlantic coastline, with subsequent nested elimination of genetic diversity and increasing genetic differentiation at the northern range margin.